2009
DOI: 10.1136/jech.2007.070292
|View full text |Cite
|
Sign up to set email alerts
|

Gender, health inequalities and welfare state regimes: a cross-national study of 13 European countries

Abstract: Background: This study is the first to examine the relationship between gender and self-assessed health (SAH), and the extent to which this varies by socioeconomic position in different European welfare state regimes (Liberal, Corporatist, Social Democratic, Southern). Methods: The EUROTHINE harmonised data set (based on representative cross-sectional national health surveys conducted between 1998 and 2004) was used to analyse SAH differences by gender and socioeconomic position (educational rank) in differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
1
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 72 publications
(78 reference statements)
10
140
1
6
Order By: Relevance
“…Previous research reports that women report worse selfrated health than men, although the magnitude of sex differences varies across EU countries (Bambra et al 2008). It has also been demonstrated that men have superior physical performance (Jeune et al 2006;Oksuzyan et al 2010) and fewer limitations in functional abilities compared with the same-aged women .…”
mentioning
confidence: 93%
“…Previous research reports that women report worse selfrated health than men, although the magnitude of sex differences varies across EU countries (Bambra et al 2008). It has also been demonstrated that men have superior physical performance (Jeune et al 2006;Oksuzyan et al 2010) and fewer limitations in functional abilities compared with the same-aged women .…”
mentioning
confidence: 93%
“…It results in a fourfold typology of European welfare state regimes: Scandinavian (social democratic), Anglo-Saxon (liberal), Bismarckian (conservative), and Southern (see Box 1). In this article, as with our previous research on welfare state regimes and health outcomes (6,(12)(13)(14)27), we use the Ferrera typology.…”
Section: Welfare State Regimesmentioning
confidence: 99%
“…This is why the most important message concerning the issue of women's health in Slovenia and elsewhere in times of economic downturn is the vital role of welfare and health policies. Welfare states are important determinants of health and health inequalities as they mediate the extent and impact of socioeconomic position on health (16). As UK scholars point out, their country's case is particularly instructive because of the process of polarization that occurred during two decades when inequality was off the political agenda from 1979 to 1997.…”
Section: Discussionmentioning
confidence: 99%
“…The datasets we used in this case come from four time points: 1994 (N=1037), 2001 (N=1093), 2009 (N=1065) and 2012 (N=1034). For the purpose of our analysis, educational rank was used as a proxy for socioeconomic position, as is done frequently in similar surveys (16,18). Although people's socioeconomic position may be more accurately expressed by occupation or income, education lies at the heart of people's position in society because it is a fundamental determinant of both occupation and income.…”
Section: Methodsmentioning
confidence: 99%